The lowest hanging fruit: Beneficial gene knockouts in past, present, and future crop evolution - Monroe, J.G.; Arciniegas Vega, Juan Pablo; Moreno, J.L.; Sánchez, F.; Sierra, S.; Valdés, S.; Torkamaneh, D.; Chavarriaga, P. (Elsevier, 2020)
It is now well-documented that gene knockout (loss-of-function) alleles have played a prominent role in crop evolution during domestication, diversification, and improvement. This includes dramatic examples from the very origins of agriculture to the monumental yield increases of the Green Revolution. Recent advances in the generation of whole genome sequence data and functional investigations into the molecular genetic basis of crop traits continue to reveal the existence of considerable beneficial loss of function in crop species. These discoveries now inspire contemporary efforts to use targeted gene knockouts powered by modern gene editing tools to accelerate crop breeding. Here we trace the history and future of loss of function as a powerful mechanism of crop evolution and review the reasons gene knockouts might have been particularly important in past crop evolution and why they continue to be a “lowest hanging fruit” for directing crop evolution through molecular breeding in pursuit of more productive, resilient, and nutritious crops.